Collaboration in Mathematics Teacher Education: the What, How, and Why of Mathematical Modeling - Aubrey Neihaus; Amy Bennett (The Advocate, 2022)
In this paper, we share our collaboration across the disciplines of mathematics and mathematics education to develop and implement a mathematical modeling task for prospective secondary mathematics teachers. Through this collaboration, we identified three key components of mathematical modeling: the what, how, and why. In this paper, we outline these components from the literature and how each framed our development and implementation of the Sprinkler Task in our mathematics content and mathematics methods courses for secondary teachers. These three components show that mathematical modeling is a particularly fruitful space for collaboration between the disciplines of mathematics and mathematics education in teacher education.
Keywords: Modeling; Teacher Education; Mathematics Education; Collaboration